Online Traditional Malay Massage Appointment System (OTraMAS) / Izyan Farhana Anwar - Anwar, Izyan Farhana (2022)
Online Traditional Malay Massage Appointment System for kak Ilma Perubatan Tradisional (KIPT) is a system developed to manage an appointment for customers. The necessity for a good database system is triggered by communication issues and an unstructured manner of giving appointment information via social media and social communication platforms such as Whatsapp. Besides, unstructured platforms for appointments cause difficulties to both customers and the organization especially when there were problems happened. Online Traditional Malay Massage Appointment System (OTraMAS) for KIPT was developed by following the adapted Waterfall Model. The methodology consists of five phases which were requirement analysis, system design, implementation, testing, and deployment. System testing was undertaken after the construction of the Online Traditional Malay Massage Appointment System for Perubatan Kak Ilma was completed to confirm the system's functioning and efficiency. A tester will assess the functioning of a system built by a developer and mark the features of the system that perform well on a test case. There were a few recommendations that can be applied on the Online OTraMAS in the scope of the functionalities and the capabilities of the system which are added button cancel for admin and the system in future has transaction online. The system usability scale for user evaluation of OTraMAS was 73.08. Based on the general guideline on SUS score interpretation, the SUS grade for this system testing is B which was good. It is hoped that in the future OTraMAS for KIPT will be enhanced for its features to be a better online appointment website.